2010
DOI: 10.1186/1477-7525-8-118
|View full text |Cite
|
Sign up to set email alerts
|

Association between perceived chewing ability and oral health-related quality of life in partially dentate patients

Abstract: BackgroundOne of the most immediate and important functional consequences of many oral disorders is a reduction in chewing ability. The ability to chew is not only an important dimension of oral health, but is increasingly recognized as being associated with general health status. Whether perceived chewing ability and oral health-related quality of life (OHRQoL) are correlated to a similar degree in patient populations has been less investigated. The aim of this study was to examine whether perceived chewing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 27 publications
(29 reference statements)
5
62
0
5
Order By: Relevance
“…14, 15 The very limited amount of available research showed that the frequency of prosthetic reconstructions usage among ESRD patients is very low. Musacchio et al remarked about the existence of a large group of edentulous patients undergoing dialysis, who do not use dentures.…”
Section: Discussionmentioning
confidence: 99%
“…14, 15 The very limited amount of available research showed that the frequency of prosthetic reconstructions usage among ESRD patients is very low. Musacchio et al remarked about the existence of a large group of edentulous patients undergoing dialysis, who do not use dentures.…”
Section: Discussionmentioning
confidence: 99%
“…Surge como instrumento único de avaliação em 13 estudos: na Jordânia (Al Habashneh et al, 2012); no Brasil (Pereira et al, 2009); Japão (Inukai et al,2010); na China (Zheng et al, 2011); no Irão (Motallebnejad et al, 2011); Finlândia (Miettinen et al, 2012;Rusanen et al, 2012;Silvola et al, 2012); Espanha (Gil-Montoya et al, 2013;Montero et al, 2009;Perea et al, 2013); Nova Zelândia (Thomson et al, 2006) e com indivíduos croatas e eslovenos (RenerSitar et al, 2008). É utilizado em simultâneo com outro instrumento numestudo desenvolvido noCanadá por Locker e Gibson (2005).…”
Section: Resultsunclassified
“…Destaca-se a utilização da variável referente à presença ou número de dentes naturais presente em 10 estudos (Gil-Montoya et al, 2013;Hsu et al, 2014;Inukai et al, 2010;Locker & Gibson, 2005;Montero et al, 2008;Motallebnejad et al, 2011;Perea et al, 2013;Pistorius et al, 2013;Wright, 2009;Thomson et al, 2006;); a presença de dentes deteriorados (cariados), perdidos ou obturados e doenças periodontais em 4 estudos (Montero et al, 2008;Montero et al, 2009;Motallebnejad et al, 2011;Thomson et al, 2006); a má oclusão avaliada em 4 estudos (Hsu et al, 2014;Rusanen et al, 2012;Sardenberg et al, 2011;Silvola et al,2012); a utilização de próteses dentárias em 3 estudos (Montero et al, 2008;Perea et al, 2013;Pistorius et al, 2013;Wright et al, 2009); a xerostomia em 2 estudos (Perea et al, 2013;Thomson et al, 2006); a dor facial em 2 estudos Zheng et al, 2011); as disfunções temporomandibulares em 3 estudos (Miettinen et al, 2012;Pereira et al, 2009;Rusanen et al, 2012) e a dor de dentes em apenas 1 estudo (Rener-Sitar et al, 2008).…”
Section: Resultsunclassified
“…In a Japanese intervention study of institutionalized elderly subjects, GOHAI scores were improved when denture treatment was performed (Naito et al 2010). Another recent study reported a significant association between decreased chewing ability and decreased OHIP score (Inukai et al, 2010).…”
Section: Quality Of Lifementioning
confidence: 98%